(untitled) (Bangladesh Journal of Medical Science, 2020)
Background and Aim: The main goal of nursing is to promote the value of human beings and the dignity of all those who need care. Nursing should not only include scientific knowledge and technical skills, but also a professionin which professional values are acknowledged. The aim of this study was to determine the professional values from the viewpoint of nursing students in Jahrom University of Medical Sciences. Materials and Methods: In this descriptiveanalytical study, 120 students of Jahrom Nursing and Midwifery Faculty were selected through census sampling. A two-part questionnaire was used to assess the students’ viewpoints toward professional values: Part I: Social-demographic characteristics and Part Two: Nurses professional values scale - Revised survey tool, which consists of 26 items from professional ethics codes of the American Nursing Association and includes the following items: care (9 items), activity (5 items), trust (5 items), professionalization (4 items) and justice (3 items). The options are expressed on the basis of a five-option Likert scale, so that the option with the least importance gets score 1 and the option with the most importance gets the score 5. The range of grades will be from 26 to 130, and a higher score indicates that they are more familiar with professional values. Results: 120 nursing students participated in the present study. Mean scores of dimensions of care, pragmatism, trust, professionalism, and justice were 3.50, 3.20, 3.65, 3.45, and 3.75, respectively. Maintaining competency in the clinical setting (dimension of trust) was the most important componentand activities in professional nursing and research affairs associations (pragmatic dimension). Conclusion: In order to promote the professional development and transformation of today’s students into future capable nurses, it is imperative to develop planning and teaching methods tailored to the existing conditions and facilities, as well as to consider areas of strength and weakness in the area of professional value. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.427-432